On the type species of the genus Phoenicurusia Verity, 1943 (Lepidoptera, Lycaenidae, Lycaeninae) - Krupitsky, Anatoly V. (Zootaxa, 2017)
The purpose of this study is to clarify the identity of the type species of the lycaenine genus Phoenicurusia Verity, 1943 so that the name can be used correctly in future taxonomic work. Phoenicurusia was originally typified by Polyommatus phoenicurus Lederer, 1870 which is currently treated as a member of the genus Athamanthia Zhdanko, 1983 (Bozano & Weidenhoffer 2001). However, the specimen examined and illustrated by Verity (1943) to diagnose the genus was an individual of Polyommatus phoenicurus var. margelanica Staudinger, 1881 currently treated as a distinct species. Consequently, Verity’s original typification was based on a misidentification. In order to make Phoenicurusia available, and taking in consideration differences in the male genitalia structure supporting distinct genera Phoenicurusia and Athamanthia, its type species is fixed under Article 70.3.2 of the International Code of Zoological Nomenclature (1999) as Polyommatus phoenicurus var. margelanica.